Speech Modification by Science Teachers in Presenting Science Using English - Ivonny Rakhmawati Pellondo"u; B. Budiyono (Magister Scientiae, 2010)
This case study was conducted to explore the speech modification by science teachers in presenting science in English. There were two subjects, science teachers at the third and fourth grade levels. The data were collected by recording the teachers’ voice while they were teaching science in their class and interview protocols. The findings show that the teachers have done some points as theoretically claimed. In focus on key words, the teachers in all meeting did not introduce the new words more than twelve. Sometimes the teachers used words with personal reference in presenting the materials. Shorter and less complex sentences were also found in their teaching even though sometimes they also used complex or long sentences. Repeating or paraphrasing sentences did not show too much. The teachers asked intersperse questions almost in all the meeting to dig students’ prior knowledge or sometimes just to review the previous lesson. Most of the feedbacks were shown when students mispronounced the words or they did not know how to spell the words. As a conclusion, when the science teachers made their language more comprehensible to their students by modifying how they talked in a number of ways, the learning process becomes effective.